Concern about salient pathogen threats increases sensitivity to disgust. (February 2022) - Boggs, Shelby T.; Ruisch, Benjamin C.; Fazio, Russell H.
Abstract: Individuals vary in their sensitivity to disgust—differences that have implications for intergroup attitudes, political ideology, and beyond. However, the source of this variability in disgust sensitivity remains a subject of debate. In this work, we test the hypothesis that sensitivity to disgust is "calibrated" by an individual's concern about disease threats in their local ecology. Leveraging the COVID-19 pandemic, we obtain strong support for this hypothesis, finding that disgust sensitivity increased following the COVID-19 outbreak and that the degree of this increase was moderated by an individual's subjective concern about contracting the disease. This work fills a longstanding theoretical gap regarding the sources of variability in disgust sensitivity, while challenging the view that disgust sensitivity is an immutable individual difference. Given the role of disgust in motivating intergroup prejudice and political ideology, we anticipate that these increases in disgust sensitivity are likely to have important downstream societal implications. Highlights: Test whether disgust sensitivity is "calibrated" to individuals' perceived ecology. Cross-sectional and longitudinal studies examine disgust sensitivity after COVID-19. Disgust sensitivity generally increased. Degree of increase was moderated by concern about contracting the virus. Results challenge view that disgust sensitivity is stable and immutable.